House Environment Factors Related To The Presence Of Mosquito Larvae - Gita Sekar Prihanti; Diajeng Septi A; Faiz Zulkifli; Rachma Ferdiana; Silvia Aruma Lestari; Siti Dewi A; Umar; Zatil Aqmar; Amira Tauhida (Universitas Muhammadiyah Malang, 2022)
Background: Dengue hemorrhagic fever (DHF) is a viral infection transmitted by mosquitoes and is one of the health problems in community. DHF is currently still a health problem in Indonesia because the incidence of DHF cannot be reduced. The DHF morbidity in Indonesia in 2015 reached 50.75 per 100,000 populations, and the Incidence Rate (IR) in 2016 reached 78.85 per 100,000 populations, exceeding the national IR target (49 per 100,000 populations). The presence of mosquito larvae is an indicator of mosquitoes in an area. As a matter of fact, there are many factors that affect the presence of mosquito larvae. Objective: To determine the house environment factors related with the presence of mosquito larvae Method: Observational analytic with cross-sectional design. The sampling used cases and controls of 285 houses. The sample filled out the informed consent agreement, then the researchers gave the questionnaire, and made observations, next the researchers filled out the checklist according to the observation. The data were analyzed in bivariate technique with chi-square test, followed by multivariate test using logistic regression test. Results: The results of the multivariate test showed 7 factors that influenced the presence of larvae, consisting of the variables of PSN (Mosquito Breeding Ground Eradication) action (p = 0.012; OR = 0.022; CI = 0.001-0.435), PSN attitude (p = 0.005; OR = 1658247.9; OR: CI = 0.000-0.014), Number of people in the house (p = 0.013; OR = 0.071; CI = 1.731-113.550), Frequency of cleaning containers (p = 0.006; OR = 1139.1; CI = 0.000-0.080), Mosquito breeding sites (p = 0.006; OR = 0.006; CI = 0.424-6148.76), Fish in containers (p = 0.003; OR = 434.272; CI = 0.000-0.134), container location (p = 0.007; OR = 0.006 ; CI = 4.047- 4653.77). Conclusion: Many factors affect the presence of mosquito larvae, both in the home environment and containers owned by residents of the house. The presence of fish in containers is the most influential factor. Breeding fish as mosquito larva predators is included as parts of 3M Plus which is quite easy to do by the community. Thus, it requires maximum effort to increase knowledge of the community about these steps.